Adenomyosis in infertile women: prevalence and the role of 3D ultrasound as a marker of severity of the disease. Issue 1 (December 2016) - Puente, J.; Fabris, A.; Patel, J.; Patel, A.; Cerrillo, M.; Requena, A.; Garcia-Velasco, J.
Abstract Background Adenomyosis is linked to infertility, but the mechanisms behind this relationship are not clearly established. Similarly, the impact of adenomyosis on ART outcome is not fully understood. Our main objective was to use ultrasound imaging to investigate adenomyosis prevalence and severity in a population of infertile women, as well as specifically among women experiencing recurrent miscarriages (RM) or repeated implantation failure (RIF) in ART. Methods Cross-sectional study conducted in 1015 patients undergoing ART from January 2009 to December 2013 and referred for 3D ultrasound to complete study prior to initiating an ART cycle, or after ≥3 IVF failures or ≥2 miscarriages at diagnostic imaging unit at university-affiliated private IVF unit. Adenomyosis was diagnosed in presence of globular uterine configuration, myometrial anterior-posterior asymmetry, heterogeneous myometrial echotexture, poor definition of the endometrial-myometrial interface (junction zone) or subendometrial cysts. Shape of endometrial cavity was classified in three categories: 1.-normal (triangular morphology); 2.- moderate distortion of the triangular aspect and 3.- "pseudo T-shaped" morphology. Results The prevalence of adenomyosis was 24.4 % (n  = 248) [29.7 % (94/316) in women aged ≥40 y.o and 22 % (154/699) in women aged <40 y.o., p  = 0.003)]. Its prevalence was higher in those cases of recurrent pregnancy loss [38.2 % (26/68) vs 22.3 % (172/769), p  < 0.005] and previous ART failure [34.7 % (107/308) vs 24.4 % (248/1015), p  < 0.0001]. The presence of adenomyosis has been shown to be associated to endometriosis [35.1 % (34/97)]. Adenomyosis was diagnosed as a primary finding "de novo" in 80.6 % (n  = 200) of the infertile patients. The impact on the uterine cavity was mild, moderate and severe in 63.7, 22.6 and 10.1 % of the cases, respectively. Conclusions Our results indicate that adenomyosis is a clinical condition with a high prevalence that may affect the reproductive results. The described severity criteria may help future validating studies for better counseling of infertile couples.